Causative Factors of Respiratory Tract Disorders among Agricultural Workers - Siti Amalia Galuh Putri Mawardi; Vani Dekasari; Ida Ayu Made Sri Handayani; Enggal Hadi Kurniyawan; Kholid Rosyidi Muhammad Nur; Dicky Endrian Kurniawan; Alfid Tri Afandi; Ahmad Rifai; Titin Ratnaningsih (Health and Technology Journal (HTechJ), 2025)
Agricultural workers are particularly susceptible to respiratory ailments. This results from exposure to various harmful substances in the workplace, including dust, insecticides, and smoking. Farmers may have acute respiratory illnesses, such as upper respiratory tract infections, or chronic respiratory conditions, such as asthma and chronic obstructive pulmonary disease (COPD). This article aims to examine the literature about respiratory problems encountered by farmers. The databases utilized are Google Scholar, Semantic Scholar, and Science Direct. The specified English keywords are "Dust exposure" AND "Farmer" OR "Rice mill" AND "Lung function". Meanwhile, Indonesian keywords employ the terms "Exposure to dust" AND "Farmers" OR "Rice mill" AND "Lung function". The research findings indicate that respiratory illnesses pose a significant health issue for farmers. To prevent respiratory problems in farmers, minimizing their exposure to harmful substances in their work environment is necessary. The way to overcome this is by using Personal Protective Equipment (PPE), ensuring adequate ventilation in rice mills, and carrying out regular health checks to detect and treat respiratory problems early.